2019
DOI: 10.1590/1806-90882019000300004
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOMETRIC ANALYSIS OF FRUITS AND SEEDS OF Annona crassiflora Mart. (ANNONACEAE) FROM CENTRAL BRAZIL

Abstract: With the existing reduction of the vegetation cover of the Cerrado, several tree species have their areas of occurrence diminished, and as a consequence, they lose part of their genetic diversity. To counter this scenario it is necessary to know the genetic diversity in order to base projects and practical conservation measures. Thus, the objective of this work was to investigate the genetic variability of Annona crassiflora by means of morphometric data of fruits and seeds in four populations in central Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, araticum plants present high genetic diversity since they come from seeds that have not yet undergone genetic improvements, thus resulting in highly different individuals [ 3 ]. Moreover, several factors can affect the genetic diversity of this species, including climatic conditions (e.g., temperature), geographical location, and landscape where the matrix is located (e.g., percentage of forestry cover, water, and urban areas) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, araticum plants present high genetic diversity since they come from seeds that have not yet undergone genetic improvements, thus resulting in highly different individuals [ 3 ]. Moreover, several factors can affect the genetic diversity of this species, including climatic conditions (e.g., temperature), geographical location, and landscape where the matrix is located (e.g., percentage of forestry cover, water, and urban areas) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to reproductive morphometric differences, we suggested that fragmentation can cause these effects in the long-term. Other native, commercial and ecologically important plant species from the Cerrado showed morphometric differences between studied populations, as is the case of Dipteryx alata Vogel (BOTEZZELLI et al, 2000), Harconia speciosa Gomes (GANGA et al, 2010), Mauritia flexuosa (MATOS et al, 2014) and Annona crassiflora (PALERMO & SOUZA, 2019). This may indicate isolation of populations, caused by habitat loss and fragmentation.…”
Section: Morphometric Features Between Populationsmentioning
confidence: 81%
“…The morphometric characterization of fruits and seeds is important in taxonomic studies, identification of varieties with economic value, verification of the phenotypic and genetic variation occurrence and association with environment, both within and between plant populations (SILVA et al, 2007;FELIZARDO et al, 2015;PADILHA et al, 2016;RIOS et al, 2016). Also provides support for research on fruit production and plant propagation (SCHLINDWEIN et al, 2019), since the degradation of natural ecosystems reduces the quality of progenies on a global scale (AGUILAR et al, 2019), and in the Brazilian Cerrado (MATOS et al, 2014;PALERMO & SOUZA, 2019).…”
Section: Introductionmentioning
confidence: 99%